Acute Hemichorea Can Be the Only Clinical Manifestation of Post-Varicella Vasculopathy: Two Pediatric Clinical Cases - Davico, Chiara; Canavese, Carlotta; Tocchet, Aba; Brusa, Chiara; Vitiello, Benedetto (Frontiers in Neurology, 2018)
Acute hemichorea can occur in the context of several autoimmune and vascular neuropathologies. Primary infection by varicella zoster virus (VZV) can result in vasculopathy with neurological manifestations, such as hemiparesis, at times accompanied by hemi-chorea. Isolated hemi-chorea, however, had not been reported. We here describe two cases of VZV-induced vasculopathy whose sole clinical manifestation was acute hemi-chorea. Both cases involved young boys of 3 years of age, who presented with acute hemi-chorea 4-6 months after initial VZV infection. All hematological, immunological, and toxicological tests were normal, except for the presence of anti-VZV IgGs. Brain MRI and angio-MRI revealed specific signs of vasculitis and ischemic lesions in the basal ganglia region (lentiform nucleus, thalamus, internal capsule). Following corticosteroid and acetylsalicylic acid treatment, full symptomatic recovery was achieved within 3 weeks. Repeated MRI documented full neurostructural recovery, which was confirmed at follow-up 5-18 months later. These cases indicate that VZV-induced vasculopathy should be considered in the case of pediatric isolated acute hemichorea.